Pengaruh Motivasi, Budaya Organisasi dan Tanggung Jawab terhadap Kinerja Pegawai di Kantor Camat Jeumpa Kabupaten Bireuen - Yanti, Husni; Mangkuwinata, Denny Sumantri; Yanna, Sri (Aceh Cooperative Care, 2024)
Research examines the influence of Motivation, Organizational Culture and Responsibility on Employee Performance, with a study at the Jeumpa District Head Office. With the object of 46 employees, this is quantitative research. The data analysis technique uses a multiple linear regression approach, with the SPSS v 29 program. The analysis results show: a) partially motivation, organizational culture and work responsibility have a positive and significant effect on employee performance. b) Simultaneously organizational culture, work motivation and responsibility contribute 88.3% to the performance of Jeumpa Subdistrict office employees.